Expansion of CD103+CD69+CD8+ cytotoxic liver tissue resident memory T cells and inflammatory monocytes in advanced biliary atresia - Sibbertsen, Freya; Dress, Regine J.; Weidemann, Sören Alexander; Möller, Katharina; Herden, Uta; Fischer, Lutz; Paul, Kevin; Oh, Jun; Tolosa, Eva; Schulz-Jürgensen, Sebastian; Gersting, Søren W.; Muntau, Ania C.; et al. (Frontiers in Immunology, 2025)
IntroductionThe pathogenesis of biliary atresia (BA) is unclear to date and no therapies targeting immune regulatory pathways exist. Here we characterized potent effector liver tissue resident memory CD8+ T cells (Trm) and monocytic cells in children with advanced BA and an age-matched control group to gain insight into BA pathogenesis and immunologic regulation.MethodsLiver explants from 18 children with biliary atresia and 10 with metabolic disease and normal histology were analyzed ex vivo by multicolor flow-cytometry and immunohistochemistry. Cytokines and cytotoxic mediators were quantified by intracellular staining and bead-based arrays in culture supernatant.ResultsThe frequency of CD103+CD69+CD8+ Trm cells and CD14+CD16+ monocytes was significantly higher in BA than in the control group. In BA, T cells showed elevated expression of CD103, CD69, CD39 and production of TNF-α and Granzyme-B ex vivo, which could be reproduced in vitro by allowing cell-contact with monocytes.ConclusionsCytotoxic CD8+ Trm cells and intrahepatic monocytes might contribute to tissue destruction in BA. Therapies targeting Trm cells or the TNF-α signaling pathway could be explored to delay progression to cirrhosis in BA.